2015
DOI: 10.3109/09546634.2015.1079297
|View full text |Cite
|
Sign up to set email alerts
|

Does replacement of vitamin D reduce the symptom scores and improve quality of life in patients with chronic urticaria?

Abstract: This study support the contributing and beneficial effects of vitamin D in the treatment of CU. Replacement of vitamin D may provide improvement in both the severity of symptoms and the quality of life scores in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
3
31
0
Order By: Relevance
“…Previously, some authors reported symptom alleviation of urticaria after administration of vitamin D supplementation [15]. Our data also support this theory in different ways regarding improving health outcome, quality of life, and severity of the disease in a patient with CSU.…”
Section: Discussionsupporting
confidence: 87%
“…Previously, some authors reported symptom alleviation of urticaria after administration of vitamin D supplementation [15]. Our data also support this theory in different ways regarding improving health outcome, quality of life, and severity of the disease in a patient with CSU.…”
Section: Discussionsupporting
confidence: 87%
“…However, recent studies reported that vitamin D levels in adults are inversely correlated with chronic urticaria,15 chronic urticaria severity,16 and treatment responsiveness of patients with chronic urticaria 18. The discrepancy between ours and previous studies may be due to: (1) differences between adults and children with regard to hormone secretion as well as the uptake and utility of calcium and vitamin D;30 (2) difference in control populations, healthy controls, and controls with allergic rhinitis;15 (3) differences in vitamin D levels (since the younger generation is at risk for vitamin insufficiency in Korea,31 vitamin D insufficiency may not have a significant difference on chronic urticaria as the other population of previous studies); (4) the time of blood sampling because of seasonal variation in vitamin D level differences (since the subjects were tested at a certain time of the year, the test results may not reflect the overall vitamin D levels throughout the whole year);1617 and (5) the number of patients with chronic urticaria is small in our study (it may not be the representative value).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that chronic idiopathic urticaria is associated with infection,11 pseudo-allergy to a food,12 autoimmunity,1314 and low serum level of vitamin D 15161718. However, there is little information on the relationship of chronic urticaria with type of residence, overcrowding, socio-economic status, air pollutants, exposure to secondary smoke, and other life style factors that have established importance in other allergic diseases 121920…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a recent prospective case-control study comparing vitamin D levels in 58 chronic spontaneous urticaria (CSU) patients and 45 controls found that vitamin D levels were significantly lower in CSU patients [65]. Patients with 25[OH]D levels less than 30 ng/mL were treated with 300,000 IU/month of vitamin D3 supplementation.…”
Section: Chronic Urticariamentioning
confidence: 99%